#rebel: Rebel communication strategies in the age of social media. (November 2019) - Loyle, Cyanne E; Bestvater, Samuel E
How have rebel communication strategies been shaped by the increasingly social nature of the internet and the constant changes of information and communication technology in a Web 2.0 world? Rebel groups' ability to disseminate a message has previously been constrained by the size of the audience they could reach through traditional technologies and the costs of those technologies. Emerging social internet platforms change this dynamic by providing rebel groups with new opportunities to build and communicate to an audience. Scholars have theorized about how rebel groups adapt to these new opportunities, but to date, little systematic analysis into the phenomenon has been conducted. In this project, we present a new dataset on rebel group Twitter use and use the data to examine how armed groups use social media to communicate, the topics contained in those communications, and the audiences that consume them. Through a richer understanding of the ways in which rebel groups communicate we are better able to measure the impact of new information technologies on armed conflict in the future.